Perceptions of parents and/or caregivers regarding the aggressiveness of children with Autism Spectrum Disorder (ASD) in a child and adolescent psychosocial care center in the Federal District (DF) (Research, Society and Development, 2026)
This study aimed to investigate manifestations of aggressiveness in children with Autism Spectrum Disorder (ASD) from the perspectives of their caregivers, analyzing its forms, triggering factors, management strategies, and the influence of the intersectoral care network. This qualitative study was conducted with ten caregivers of children with ASD receiving care at a Child and Adolescent Psychosocial Care Center (CAPSi) linked to the Health Secretariat of the Federal District. Thematic analysis revealed that aggressiveness functions as an expression of emotional, sensory, or physical distress, frequently triggered by frustration, changes in routine, sensory overload, and communicative difficulties. Two central axes emerged: (1) manifestations, triggering factors, and management strategies of aggressiveness; and (2) the influence of the intersectoral care network and public policies, in which CAPSi provides the main support, while Primary Health Care, Specialized Rehabilitation Centers, schools, and extended family demonstrate limited capacity for support. The findings indicate that effective management requires individualized Therapeutic Care Plans, integration among the Psychosocial Care Network, the Care Network for Persons with Disabilities, and the educational sector, as well as actions aimed at strengthening continuous care, expanding family support, and reducing vulnerabilities that intensify childhood distress.